Chinese Family Business and Issues of Succession and Human Resource Management - WANG, Wei (2008)
The Chinese family business (CFB) is heavily influenced by traditional Confucian ideology and is currently facing more and more challenges in succession and human resource management in rapid developing age.Thus, this dissertation aims to conclude those challenges from existed literature and try to explore some feasible solutions through four qualitative case studies in typical successful Chinese family businesses in HongKong, Singapore and Chinese mainland. After the detailed research and analyses, this dissertation found the CFBs could accomplish smooth succession successfully and could be professional managed and developed while in traditional combination of management and family control.